Diagnostic performance of multidetector computed tomography for symptomatic lymphoceles in kidney transplant recipients - Heungman Jun; Sung Ho Hwang (Korean Journal of Transplantation, 2019)
Background : To evaluate the size of a postoperative lymphocele in the coronal and axial reconstruction planes using multidetector computed tomography (MDCT) in kidney transplantation recipients. Methods : We evaluated 92 recipients who underwent MDCT of the abdominopelvis at 1 month after kidney transplantation. The axial short axis, axial surface area, coronal short axis, and coronal surface area of the lymphocele were measured using the reconstructed MDCT coronal and axial images. Depending on the clinical manifestations and radiologic findings of the recipients, all lymphoceles were classified into symptomatic and asymptomatic. We compared the suitability of the size measurement on coronal and axial planes of MDCT reconstruction for symptomatic lymphocele in kidney transplant recipients using Spearman's correlation analysis and comparisons of receiver operating characteristic (ROC) curves. Results : Areas under the ROC curves were 0.957 and 0.928 for the axial short axis and axial surface area and 0.968 and 0.966 for the coronal short axis and coronal surface area, respectively. In pairwise comparison of the ROC curve of the parameters of the symptomatic lymphoceles, the coronal measurement was significant in contrast to the axial measurement (short axis, P=0.357; surface area, P=0.047). Conclusions: For the prediction of symptomatic lymphoceles using MDCT, the coronal measurement of postoperative lymphoceles can significantly improve diagnostic performance over axial measurement in kidney transplant recipients.